Formation Distribution and Geological Significance of Ferric Stromatolites - Chen, Wenyan (International Journal of Natural Resources and Environmental Studies, 2026)
Ferric stromatolites are microbialites formed by cyanobacteria and other microorganisms under specific geological conditions. Their unique layered structure and iron-bearing composition are of great significance for understanding microbial evolution and mineral genesis. With the continuous advancement and improvement of exploration technologies and research methods, ferric stromatolites will play an increasingly prominent and important role in iron ore resource exploration. Therefore, this paper summarizes the basic concepts of ferric stromatolites, outlines their research value, research methods, formation mechanisms, geological distribution and exploration significance in geology, and draws corresponding conclusions.